VISCERAL LEISHMANIASIS IN A CAPTIVE CRAB-EATING FOX CERDOCYON THOUS - Tenorio, Michely da Silva [UNESP]; de Oliveira e Sousa, Lucio; Paixao, Mirian dos Santos [UNESP]; Alves, Maria Fernanda [UNESP]; Paulan, Silvana de Cassia [UNESP]; Lima, Flavia Luna [UNESP]; Gomes Jusi, Marcia Mariza [UNESP]; Tasca, Karen Ingrid; Machado, Rosangela Zacarias [UNESP]; Starke-Buzetti, Wilma Aparecida [UNESP] (Amer Assoc Zoo Veterinarians, 2011)
Visceral leishmaniasis (VL) is a zoonotic disease with worldwide distribution. The crab-eating fox (Cerdocyon thous) is considered a wild reservoir of many zoonotical diseases, particularly VL. This study reported the presence of Leishmania infantum amastigotes in different organs of one captive C. thous found dead in a zoo. This animal was positive by the indirect fluorescence antibody test and had many clinical signs of VL. Intracellular amastigote forms of L. infantum were seen in neutrophils and macrophages in sample tissues from skin, lymph nodes (popliteal, submandibular, prescapular, and mesenteric), spleen, and liver. The numbers of positive cells and intracellular parasites were higher in macrophages than in neutrophils. In addition, polymerase chain reaction demonstrated extensive distribution of Leishmania DNA in C. thous tissues from multiple organs. The presence of intracellular amastigotes in neutrophils and macrophages as well as DNA of the parasite in tissues, specifically skin demonstrate that this crab-eating fox is an adequate host for L. infantum and reinforce the importance of VL for symptomatic wild canids kept in captivity in endemic areas.
Keywords: Cerdocyon thous; crab-eating fox; Leishmania infantum; Visceral Leishmaniasis